2021
DOI: 10.1177/14613557211032603
|View full text |Cite
|
Sign up to set email alerts
|

Police self-legitimacy and democratic orientations: Assessing shared values

Abstract: Using a sample of frontline police officers from several mid-sized municipal police departments in the United States, this study explores the relationships between frontline police officers’ self-legitimacy, organizational fit, moral alignment with policed communities, and attitudes toward democratic policing principles. Using partial least squares structural equation modeling, the analysis frames democratic policing using a formative latent construct to test several hypotheses. The results support a direct po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In addition, police accountability considers law enforcement and is associated with police responsibility for efficiently providing services of maintaining law and order and controlling crimes by fairly treating individuals under the jurisdiction of the laws (Ojedokun, Ogunleye, & Aderinto, 2021). White et al (2021) reported that police could enhance trust among the citizens by increasing legitimacy, ensuring community ownership, continuously improving their services, and ensuring law and order situations in this country.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, police accountability considers law enforcement and is associated with police responsibility for efficiently providing services of maintaining law and order and controlling crimes by fairly treating individuals under the jurisdiction of the laws (Ojedokun, Ogunleye, & Aderinto, 2021). White et al (2021) reported that police could enhance trust among the citizens by increasing legitimacy, ensuring community ownership, continuously improving their services, and ensuring law and order situations in this country.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…In a democratic society, institutions' role, especially police institutions, is vital and significant (White, Kyle, & Schafer, 2021). Research broadly recognize the significance of frontline police officers' attitude and behaviors in establishing peace and harmony and implementing the law and order situation in a country (Blair et al, 2021).…”
mentioning
confidence: 99%
See 3 more Smart Citations